Kisah Perempuan Pekerja Migran Indonesia di Hong Kong: Perjuangan untuk Keluarga dan Pendidikan Anak - Wahidah Zein Br Siregar (State Islamic University (UIN) of Sunan Ampel, 2020)
This study aims to describe struggle of Nurdiana and Tira, two Indonesian female migrant workers who work in domestic sector in Hong Kong. They are part of thousands of Indonesian migrant workers in this country. Data from BNP2TKI shows that in 2019 only, there were 70,840 migrant workers placed in Hong Kong. Most of them are women. These women work in informal sectors, particularly domestic works. Using life story method, this research is able to find out that the main reason for both Nurdiana and Tira to work in Hong Kong is to fulfill their family needs and support education of their children. Their children are studying in Pesantren. Life story gives chances to both informants to talk more about their work, their relation with employers, family, friends, and challenges they face, including that of COVID-19. Their stories provide an understanding of the real situation faced by these two family heroes.